2016
DOI: 10.1021/acs.jpcc.6b02028
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Substituted Benzene Derivatives on Silica: Effects of Electron Withdrawing and Donating Groups

Abstract: A fundamental understanding of the forces that drive uptake and binding of aromatic molecules on well-characterized surfaces such as silica is important for predicting the fate of toxic industrial compounds in the environment. Therefore, the adsorption of simple substituted benzene derivatives has been investigated on a hydroxyl-functionalized surface to probe the effects of electron withdrawing and donating functional groups on gas–surface binding. Specifically, this work probes how methyl and halide function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 57 publications
4
30
0
Order By: Relevance
“…Based on similar results, previous infrared studies have also reported the presence of hydrogen bonding between other molecules and the SiO 2 surface. 20 , 33 , 34 A detailed peak assignment for limonene adsorbed on hydroxylated SiO 2 is provided in the ESI (Table S1 † ) and shows that the vibrational frequencies are close to that for limonene in the gas and liquid phases.…”
Section: Resultsmentioning
confidence: 89%
“…Based on similar results, previous infrared studies have also reported the presence of hydrogen bonding between other molecules and the SiO 2 surface. 20 , 33 , 34 A detailed peak assignment for limonene adsorbed on hydroxylated SiO 2 is provided in the ESI (Table S1 † ) and shows that the vibrational frequencies are close to that for limonene in the gas and liquid phases.…”
Section: Resultsmentioning
confidence: 89%
“…42 Such an interaction has been observed previously in gas adsorption studies of benzene and toluene onto SiO2. 43 Unlike the dynamics, the partitioning behavior of polymer into the interstitial voids of the nanoparticle packings in the SIP system does not strongly depend on the confinement ratio (Figure 4). We believe that the independence of partitioning on the confinement ratio is attributed to the fact that, at long times, the concentration within the pores exceeds the critical overlap concentration.…”
Section: Resultsmentioning
confidence: 95%
“…This result can be understood by similar benzene adsorption studies on silica surfaces. Benzene adsorption on silica is strongly affected by the concentration of surface silanol groups due to the hydrogen bonding between surface silanol groups and the π electrons of benzene . The heat of adsorption of benzene on silica with different surface chemistries has been shown to follow the order of surface‐hydroxylated silica > surface‐dehydroxylated silica > surface‐silylated silica, since surface dehydroxylation and surface silylation decrease the density of surface silanol groups.…”
Section: Resultsmentioning
confidence: 99%